2013
DOI: 10.1111/cns.12134
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Modulation of Acute Nociception Involves Regulation of Nav1.8 in Primary Afferent Neurons in Mice

Abstract: Our results indicate that histamine participates in acute pain modulation in a dose-related manner. The regulation of Nav 1.8 expression and the excitability of nociceptive primary afferent neurons may be involved in the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Interestingly, this increased expression was inhibited only by H2 receptor blockers (e.g., famotidine) and not by antagonists of H1 or H3 receptors. These findings are consistent with those of Yu et al [122]. …”
Section: How Do Pharmacological Interventions Take Advantage Of Pasupporting
confidence: 94%
“…Interestingly, this increased expression was inhibited only by H2 receptor blockers (e.g., famotidine) and not by antagonists of H1 or H3 receptors. These findings are consistent with those of Yu et al [122]. …”
Section: How Do Pharmacological Interventions Take Advantage Of Pasupporting
confidence: 94%
“…Itch and pain are two distinct somatic sensations, but they also share many similarities [4;18;29;34;36;47;68;69]. Itch evokes scratching response, while pain elicits withdrawal reflex [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of histamine in neuropathic pain is not fully understood yet. Previously, we reported that, for the first time, histamine might regulate Nav1.8 expression under physiological condition , whereas whether histamine regulates Nav1.8 expression after nerve injury remains unclear. Therefore, the present study was designed to investigate the effect of histamine on Nav1.8 expression in primary afferent neurons in vitro and in vivo and the type of histamine receptors that mediates this effect.…”
Section: Introductionmentioning
confidence: 96%